2011
DOI: 10.1590/s1677-55382011000500012
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin A for the treatment of neurogenic detrusor overactivity in multiple sclerosis patients

Abstract: Purpose: Neurogenic detrusor overactivity (NDO) is common in patients who suffer from multiple sclerosis (MS). When the usual pharmacological treatment fails, botulinum toxin type A (BTX-A) injections can be proposed. The safety and efficacy of this treatment are already well known, but only a few studies focus on its use in patients with MS. Materials and Methods: Seventy-one patients with MS underwent their first BTX-A injection for refractory NDO. They had clinical and urodynamic cystometry assessment befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…However, those with the 300 U dose had more adverse events (AEs) (see Adverse reactions/complications section). In summary, there have been a number of excellent review articles 34,41,49,50 and clinical studies, 17,18,37,38,42,43,45,46 confirming the effectiveness of BoNT in those with NDO. Results of a number of clinical studies using BoNT/A in adults with DO due to a neurogenic cause are shown in Table 2.…”
Section: Described Results Onmentioning
confidence: 92%
See 1 more Smart Citation
“…However, those with the 300 U dose had more adverse events (AEs) (see Adverse reactions/complications section). In summary, there have been a number of excellent review articles 34,41,49,50 and clinical studies, 17,18,37,38,42,43,45,46 confirming the effectiveness of BoNT in those with NDO. Results of a number of clinical studies using BoNT/A in adults with DO due to a neurogenic cause are shown in Table 2.…”
Section: Described Results Onmentioning
confidence: 92%
“…47 Therefore, these authors conclude that injection therapy should be considered as soon as anticholinergic medications fail to control NDO in those with MS rather than waiting until potentially irreversible histological and neurological damage has occurred. 45 Kuo reported on a prospective study involving the impact of BoNT on NDO not only in those with SCI but also in those with chronic cerebrovascular accident (CVA). Several concepts regarding the use of BoNT in those with a CVA were learned in this study.…”
Section: Described Results Onmentioning
confidence: 99%
“…Rufin [43] 300 U 71 *Mean MCC *Complete continence was reported in 46% of the patients. Ginsberg [39] 200/300 U 416 *MCC *The improvement in MCC and MDP during the first *MDP at the time of first involuntary detrusor contraction following treatment was better involuntary bladder than that in the placebo group (p=0.001).…”
Section: Deffontainesmentioning
confidence: 96%
“…In a series of 71 patients with MS, Deffontaines et al [43] administered 300 U of BTX type A injection, and they reported that urinary incontinence disappeared and that no NDO was observed in urodynamic examinations in 46% of the patients; 50% improvement was obtained in 31% of the patients, and no significant change was observed in 23% of the patients. In this series, it was mentioned that the mean maximum bladder capacity increased from 240 cc to 328 cc (p<0.001) and that the mean maximum detrusor pressure decreased from 61 cmH 2 O to 36 cmH 2 O.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In addition, CIC was required in 10% of the placebo group, 35% of the 200 IU onaBoNT-A group, and 42% of the 300 IU onaBoNT-A group due to urinary retention. In a study including 71 MS patients, Deffontaines-Rafin et al (32) reported that UUI disappeared in 46% of the patients, NDO was not observed in urodynamic examinations, half-and-half improvement was achieved in 31% of cases, and a significant change was not detected in 23% of the patients, with the 300 IU onaBoNT-A injections. The mean MBC was increased from 240 cc to 328 cc (p<0.001), and the MDP was decreased from 61 cmH 2 O to 36 cmH 2 O after injections.…”
Section: Ginsberg Et Al (31) Published a Study Including 416 Patientmentioning
confidence: 97%